STAT3 mediates CAF-induced osimertinib resistance via regulating protein secretion in non-small cell lung cancer - Fan, Xuchen; Wu, Sheng; Wu, Honglong; Huang, Yingying; Tong, Xuhui; Yu, Meiling; Liu, Zhe (Frontiers in Pharmacology, 2025)
IntroductionEGFR-TKI resistance is an important factor limiting the clinical application of targeted drugs in NSCLC, but the mechanism remains unclear. The tumor microenvironment is the internal environment for cancer cells to survive, and it plays an important role in tumor resistance.MethodsIn vitro assays: CCK-8 assay, wound healing, Transwell and Colony formation assay. Protein expression analyzed via Western blot. In vivo antitumor efficacy assessed by xenograft study. Target expression in tumors confirmed by immunohistochemical staining. Statistical analysis used t-test/ANOVA (p<0.05).ResultsThis study discovered that cancer associated fibroblasts (CAFs) in the tumor microenvironment induce Osimertinib resistance in NSCLC, and further study revealed that CAF-induced Osimertinib resistance in NSCLC is realized through its protein secretion. Interestingly, STAT3 is the key factor regulating CAF activation and secretion. Knockdown of STAT3 can block the secretory function of CAF, thereby reversing Osimertinib resistance in lung cancer. Furthermore, we blocked STAT3 activation in CAF with the novel STAT3 small molecule inhibitor LL1. LL1 effectively reversed CAF induced osimertinib resistance in NSCLC.DiscussionThis project contributes to a deeper understanding of the molecular mechanism of tumor microenvironment mediated EGFR-TKI resistance in NSCLC, and provides theoretical basis and experimental data for the development of novel resistance reversal agents against the tumor microenvironment.